(untitled) (Sciences & Technology. A, exactes sciences, 2005)
Superconducting YBa2Cu3O7-δ (Y-123) ceramics were prepared by the solid-state reaction method. The microstructure and superconducting properties of the sintered samples obtained under various conditions were investigated by means of X-ray diffraction (XRD), scanning electron microscopy (SEM), thermal analysis (TDA-TGA) and electrical resistivity measurements. The study showed that the calcination at 800°C for 30 hours of theY2O3, BaCO3 and CuO mixture led to the starting of the Y-123 and BaCuO2 phases’ formation. However, in the temperature range of 950 - 990°C, Y-123 crystallized and became predominate compound. For higher temperatures (near 1100°C), green Y2BaCuO5 phase was formed. A (00l) preferred orientation of Y-123 grains was occured after sintering in air at temperatures 950-990°C for 30 hours. The textured samples presented the best transport properties